2016
DOI: 10.1590/0034-7167-2016-0408
|View full text |Cite
|
Sign up to set email alerts
|

Violência por parceiro íntimo na adolescência: uma análise de gênero e geração

Abstract: Objective: to analyze the intimate partner violence in adolescence from the perspective of gender and generation. Method: Quantitative, descriptive, and exploratory research. 111 adolescents participated in this study, with ages from 15 to 19 years old. Results: We found that 91% of participants have perpetrated and 90.1% have undergone at least one of the natures of violence. The intimate partner violence in adolescence constitutes a form of gender violence, and gender constructions have determined the suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 13 publications
1
7
1
18
Order By: Relevance
“…In line with previous exploratory studies, our findings indicated that female as well as male adolescents were both victims and perpetrators of intimate partner violence. This corroborated previous studies’ results in which the rates of victimization and perpetration of violence were similar between sexes (Alegría del Ángel & Rodríguez Barraza, 2015; Brancaglioni & Fonseca, 2016; Flores Palacios et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous exploratory studies, our findings indicated that female as well as male adolescents were both victims and perpetrators of intimate partner violence. This corroborated previous studies’ results in which the rates of victimization and perpetration of violence were similar between sexes (Alegría del Ángel & Rodríguez Barraza, 2015; Brancaglioni & Fonseca, 2016; Flores Palacios et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Embora exista, nos artigos revisados, uma percepção causal entre o fenômeno da violência e o consumo de álcool, entende-se que o álcool apenas potencializa as situações de violência na conjugalidade (Vieira, Cortes, Padoin, Souza, Paula, & Terra, 2014). Ainda, a permanência de mulheres em relações violentas está associada às expectativas sociais de casamento e constituição da família (Brancaglioni, & Fonseca, 2016), além do medo de ameaças constantes e a esperança de que o companheiro modifique sua conduta (Zancan, Wassermann, & Lima, 2013).…”
Section: Discussionunclassified
“…Another socially constructed inequality concerns the freedom and sexual encouragement of boys in addition to the prohibition on girls so that when they violate these rules, they are more often faced with conflicts and violence (33)(34) . It noteworthy that the experience of violence, regardless of the forms of expression, has consequences for the victims' mental and behavioral health.…”
Section: Discussionmentioning
confidence: 99%